Classroom Design Strategies for Improving Listening Comprehension in Digital Learning Contexts - Videlindah Ani Sophiandry Haan; Johnson Welem Haan; Joko Priyana (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2026)
In the digital era, English learning has increasingly integrated online platforms and digital technologies, making it essential to create a conducive classroom environment to support effective learning, particularly in improving students’ listening skills; therefore, this study aims to review current research on how digital tools and strategies enhance the listening learning process in schools. This study employs a qualitative descriptive approach through a literature review, with data collected from journal articles, books, conference papers, and online sources published between 2014 and 2024, and analyzed using thematic content analysis to identify key tools, strategies, and challenges in integrating digital media into listening instruction. The findings indicate that digital tools such as YouTube, Podcasts, and other applications significantly improve students’ listening skills by providing authentic, engaging, and interactive learning experiences, enhancing motivation, comprehension, and overall learning quality, although their effectiveness largely depends on teachers’ ability to select appropriate content and design meaningful activities. In conclusion, integrating digital technologies can create a more conducive learning environment and improve students’ listening proficiency; however, teachers must adapt to ongoing technological changes, develop creative teaching strategies, and engage in continuous professional development to maximize learning outcomes in the digital era.